Kartini Kendeng's Resistance Movement for Environmental Preservation in the #KendengMelawan Movement on Social Media - Hari, Cahyaratri Kinasih (Bina Nusantara University, 2023)
The research focused on women who joined as Kartini Kendeng in motion #Kendengmelawan due to the development policy of cement factories in Kendeng, Rembang, Central Java. Movement of feminism from time to time had grown according to their respective fields, including women’s awareness of sustainability ecology or ecofeminism. Technological progress, which gave birth to the media, had a turn of thought women environmental to make social media a means of conveying education and campaigning, which shifted to the development of the sustainability of nature. The research was a qualitative study with the approach ethnography digital, namely observing activity movement Kartini Kendeng in social media of whatever posted page for Instagram, Twitter, and Youtube. The research has found that Kartini Kendeng is active in the campaign and fights through the support from various parties to be with the emergence of resistance activities. This indicates that Kartini Kendeng makes media as a way against the development that is considered threatening environment, do ecofeminism practices that reach the numerous and widely to do support or come with in opposition and win.